Macrometric features of the human embryonic spinal cord - Shkolnikov , V.S.; Prykhodko , S.O.; Zalevsky , L.L.; Danylevych , V.P.; Radoha , R.V. (Морфологія / Morphologia / Morfologìâ, 2025)
Background. Embryology is among the most current and widely studied fields of medicine. It can rightly be regarded as one of the key branches of both medicine and biology. Advances in embryology have enabled a deeper understanding of organismal development, the origins of congenital anomalies, and potential approaches to infertility treatment. The central nervous system plays a fundamental role in regulating and coordinating the functions of all physiological systems within the human body. As the principal regulatory and integrative structure, the central nervous system underpins the harmonious functioning of the organism, maintaining its integrity as a single, unified system. Objective of our study was to establish the macrometric parameters of the human embryonic spinal cord in the prenatal period. Methods: morphometric, anatomical and statistical. The object of the study was 10 human embryos aged 5-9 weeks of prenatal ontogenesis without malformations. The results of our study indicate that during the embryonic period, the development of the spinal cord is characterized by uneven growth across its different regions. Additionally, periods of both gradual and accelerated growth were observed. Notably, the most pronounced rapid growth occurred in embryos at 8–9 weeks of gestation. We concluded that the development of the spinal cord is characterized by an uneven rate of growth.